De novo variants in SNAP25 cause an early-onset developmental and epileptic encephalopathy. - Klöckner, Chiara; Sticht, Heinrich; Zacher, Pia; Popp, Bernt; Babcock, Holly E; Bakker, Dewi P; Barwick, Katy; Bonfert, Michaela V; Bönnemann, Carsten G; Brilstra, Eva H; Chung, Wendy K; Clarke, Angus J; et al. (Genet Med, 2021)
PURPOSE: This study aims to provide a comprehensive description of the phenotypic and genotypic spectrum of SNAP25 developmental and epileptic encephalopathy (SNAP25-DEE) by reviewing newly identified and previously reported individuals. METHODS: Individuals harboring heterozygous missense or loss-of-function variants in SNAP25 were assembled through collaboration with international colleagues, matchmaking platforms, and literature review. For each individual, detailed phenotyping, classification, and structural modeling of the identified variant were performed. RESULTS: The cohort comprises 23 individuals with pathogenic or likely pathogenic de novo variants in SNAP25. Intellectual disability and early-onset epilepsy were identified as the core symptoms of SNAP25-DEE, with recurrent findings of movement disorders, cerebral visual impairment, and brain atrophy. Structural modeling for all variants predicted possible functional defects concerning SNAP25 or impaired interaction with other components of the SNARE complex. CONCLUSION: We provide a comprehensive description of SNAP25-DEE with intellectual disability and early-onset epilepsy mostly occurring before the age of two years. These core symptoms and additional recurrent phenotypes show an overlap to genes encoding other components or associated proteins of the SNARE complex such as STX1B, STXBP1, or VAMP2. Thus, these findings advance the concept of a group of neurodevelopmental disorders that may be termed "SNAREopathies."
Keywords: Brain Diseases; Child, Preschool; Epilepsy; Humans; Intellectual Disability; Neurodevelopmental Disorders; Phenotype; Synaptosomal-Associated Protein 25

CTCF variants in 39 individuals with a variable neurodevelopmental disorder broaden the mutational and clinical spectrum. - Konrad, Enrico D H; Nardini, Niels; Caliebe, Almuth; Nagel, Inga; Young, Dana; Horvath, Gabriella; Santoro, Stephanie L; Shuss, Christine; Ziegler, Alban; Bonneau, Dominique; Kempers, Marlies; Pfundt, Rolph; et al. (Genet Med, 2019)
PURPOSE: Pathogenic variants in the chromatin organizer CTCF were previously reported in seven individuals with a neurodevelopmental disorder (NDD). METHODS: Through international collaboration we collected data from 39 subjects with variants in CTCF. We performed transcriptome analysis on RNA from blood samples and utilized Drosophila melanogaster to investigate the impact of Ctcf dosage alteration on nervous system development and function. RESULTS: The individuals in our cohort carried 2 deletions, 8 likely gene-disruptive, 2 splice-site, and 20 different missense variants, most of them de novo. Two cases were familial. The associated phenotype was of variable severity extending from mild developmental delay or normal IQ to severe intellectual disability. Feeding difficulties and behavioral abnormalities were common, and variable other findings including growth restriction and cardiac defects were observed. RNA-sequencing in five individuals identified 3828 deregulated genes enriched for known NDD genes and biological processes such as transcriptional regulation. Ctcf dosage alteration in Drosophila resulted in impaired gross neurological functioning and learning and memory deficits. CONCLUSION: We significantly broaden the mutational and clinical spectrum ofCTCF-associated NDDs. Our data shed light onto the functional role of CTCF by identifying deregulated genes and show that Ctcf alterations result in nervous system defects in Drosophila.